Stress responses during aerobic exercise in relation to motivational dominance and state - Thatcher, J.; Kuroda, Y.; Legrand, F. D.; Thatcher, R. (Journal of Sports Sciences, 2011)
We examined the hypothesis that congruence between motivational dominance and state results in optimal psychological responses and performance during exercise. Twenty participants (10 telic dominant and 10 paratelic dominant) rated their stress at 5 min intervals as they cycled on an ergometer at gas exchange threshold for 30 min in both telic and paratelic state manipulated conditions. Participants then performed a test to exhaustion at a resistance equivalent to 110% of VO2max. The hypothesized interaction between condition and dominance was significant for internal tension stress, as paratelic dominants were more stressed than telic dominants when exercising in the telic state and telic dominants were more stressed than paratelic dominants when exercising in the paratelic state. Similarly, the condition×dominance interaction for internal stress discrepancy was significant, as paratelic dominants reported greater internal stress discrepancy exercising in the telic compared with the paratelic state. Findings are discussed in relation to the application of reversal theory for understanding stress responses during aerobic exercise.